Psychoactive Effects of Lactobacillus johnsonii Against Restraint Stress-Induced Memory Dysfunction in Mice Through Modulating Intestinal Inflammation and permeability—a Study Based on the Gut–Brain Axis Hypothesis - Wang, Hesong; He, Shunhui; Xin, Jinge; Zhang, Tao; Sun, Ning; Li, Lianxin; Ni, Xueqin; Zeng, Dong; Ma, Hailin; Bai, Yang (Frontiers in Pharmacology, 2021)
Though the underlying mechanism remains elusive, a close relationship between psychological stress and intestinal inflammation has been widely accepted. Such a link is very important to set the basis for our understanding of the critical role of gut-brain axis (GBA) in homeostatic processes in health and disease. Probiotics that could confer benefits to mental health through GBA are referred to as “psychobiotics”. This study aimed to further determine whether a potential psychobiotic strain, Lactobacillus johnsonii BS15 could prevent memory dysfunction in mice induced by psychological stress through modulating the gut environment, including intestinal inflammation and permeability. Memory dysfunction in mice was induced by restraint stress (RS), one of the most commonly utilized models to mimic psychological stress. The mice were randomly categorized into three groups including no stress (NS), restraint stress (RS), and probiotic (RS-P) and administered with either phosphate buffered saline (NS and RS groups) or L. johnsonii BS15 (RS-P group) every day from day 1 to 28. From days 22 to 28, the mice in RS and RS-P groups were subjected to RS each day. Results revealed that BS15-pretreatment enhanced the performance of RS-induced mice during three different behavioral tests for memory ability and positively modulated the hypothalamic–pituitary–adrenal axis by attenuating the serum corticosterone level. In the hippocampus, L. johnsonii BS15 positively modulated the memory-related functional proteins related to synaptic plasticity, increased neurotransmitter levels, and prevented RS-induced oxidative stress and mitochondria-mediated apoptosis. In the intestines, L. johnsonii BS15 protected the RS-induced mice from damaged gut barrier by enhancing the mRNA levels of tight junction proteins and exerted beneficial effects on the anti-inflammatory cytokine levels reduced by RS. These findings provided more evidence to reveal the psychoactive effect of L. johnsonii BS15 against memory dysfunction in RS-induced mice by modulating intestinal inflammation and permeability.